Capital Structure, Compensation and Incentives - Douglas, Alan V. S. (Review of Financial Studies, 2006)
This article illustrates an incentive-aligning role of debt in the presence of optimal compensation contracts. Owing to information asymmetry, value-maximizing compensation contracts allow managerial rents following high investment outcomes. The manager has an incentive to increase these rents by choosing investments that generate greater information asymmetry. An aptly chosen debt level mitigates this incentive, because investments that generate greater information asymmetry have more volatile outcomes. The greater volatility would make the debt risky, causing the shareholders to focus on high outcomes and therefore compensation contracts that reduce managerial rents. At the optimum, the manager avoids opportunistic investments, and the shareholders offer value-maximizing compensation contracts. Empirically, the analysis predicts a negative relationship between leverage and market-to-book that is reversed at extreme market-to-book ratios, a negative relationship between leverage and profitability, a negative relationship between leverage and pay-for-performance, and a positive relationship between pay-for-performance and investment opportunities.